(untitled) (Revista de Ciências Agroveterinárias, 2012)
The reactive rock phosphates have been used as an alternative phosphorus (P) source for the irrigated rice culture in Rio Grande do Sul State. The extractor Mehlich-1 is used as the standard method for the assessment of the P availability. It can present satisfactory results when the fertilization of P in soil is carried out with a soluble source, but it can be inadequate for soils fertilized with rock phosphate, because of the possibility of dissolution of excessive reactive particles by this extractor. In order to evaluate the soil P availability in soils fertilized with rock phosphate, a greenhouse experiment on the campus of PUC, RS Uruguaiana in the period between September-October 2009 was carried out with four soils fertilized with four phosphate rates, where rice was cultivated for a 40 day period. The soil P availability was studied by the following extraction methods: anion exchange resin (AER), Mehlich-1 and Mehlich-3. The levels of available P extracted were assessed by different extractors after the incubation period. During the flooding, we analyzed the concentrations of Fe, Ca and P and the pH of the soil solution. After 40 days of flooding, the production of dry matter and P concentration were assessed in the plants’ shoots. The determination coefficients between the P accumulated by the plants and the content determined by the extraction methods were: 0.84 (anion exchange resin); 0.58 (Mehlich-1) and 0.61 (Mehlich-3). The results indicated that the anion exchange resin was more effective for predicting P availability for the irrigated rice culture in soil fertilized with rock phosphates. The separation of soils into groups according to the source material and the content of iron oxides of low crystallinity extracted with oxalate at pH 6.0, resulted in improved effi ciency of all tested methods to assess P availability for rice in soil fertilized with phosphate rock.